2014
DOI: 10.1161/atvbaha.114.303863
|View full text |Cite
|
Sign up to set email alerts
|

α5β1 Integrin Signaling Mediates Oxidized Low-Density Lipoprotein–Induced Inflammation and Early Atherosclerosis

Abstract: Objective Endothelial cell activation drives early atherosclerotic plaque formation. Both fibronectin deposition and accumulation of oxidized LDL (oxLDL) occur early during atherogenesis and both are implicated in enhanced endothelial cell activation. However, interplay between these responses has not been established. The objective of our study was to determine whether endothelial matrix composition modulates the inflammatory properties of oxLDL. Approach and Results We now show that oxLDL-induced NF-κB act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
129
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 48 publications
3
129
0
1
Order By: Relevance
“…6 B and D). These data demonstrate the importance of integrin α5 in atherogenesis in the Ldlr −/− mice, similar to that in Apolipoprotein E-deficient (Apoe −/− ) mice, reported by Yurdagul et al (16).…”
Section: Ec Dysfunction In Atheroprone Regions In Vivo Is Integrin α5-supporting
confidence: 90%
See 2 more Smart Citations
“…6 B and D). These data demonstrate the importance of integrin α5 in atherogenesis in the Ldlr −/− mice, similar to that in Apolipoprotein E-deficient (Apoe −/− ) mice, reported by Yurdagul et al (16).…”
Section: Ec Dysfunction In Atheroprone Regions In Vivo Is Integrin α5-supporting
confidence: 90%
“…In our studies, we used the WD-fed Ldlr −/− model to test the role of integrin α5 in atherogenesis. The study by Yurdagul et al (16) also demonstrated the important role of integrin α5 activation for the atherogenic process using the Apoe −/− model; they found that α5 activation could also occur via a different mechanism that involved OxLDL (16). The fact that integrin α5 was demonstrated to play an obligatory role in atherogenesis in two different murine models (i.e., Ldlr −/− and Apoe −/− ), and can be activated by two different mechanisms (i.e., atheroprone flow and OxLDL), adds to the confidence that this pathway is highly relevant in vivo.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…4,6 Cell culture models suggest that transitional matrix proteins enhance the endothelial proinflammatory response to multiple atherogenic risk factors, including both shear stress and oxidized low-density lipoprotein (oxLDL). 4,7 Transitional matrix proteins enhance shear stress-induced endothelial cell activation by promoting p21-activated kinase 2 (PAK2) signaling, which activates the transcription NF-kB to drive proinflammatory gene expression (ie, ICAM1 and VCAM1). 5,8 Limiting fibronectin deposition, either genetically or through peptide inhibitors, blunts endothelial proinflammatory signaling (PAK2, NF-kB) and gene expression both in models of acute disturbed flow-induced vascular inflammation (partial carotid ligation) and models of dietinduced spontaneous atherosclerosis.…”
mentioning
confidence: 99%
“…5,8 Limiting fibronectin deposition, either genetically or through peptide inhibitors, blunts endothelial proinflammatory signaling (PAK2, NF-kB) and gene expression both in models of acute disturbed flow-induced vascular inflammation (partial carotid ligation) and models of dietinduced spontaneous atherosclerosis. 7,9,10 The integrin family of matrix receptors consists of 18 a and 8 b subunits that assemble into 24 different integrin heterodimers with distinct matrix-binding affinities and signaling properties. 11 Fluid shear stress activates multiple endothelial cell integrins, including the collagen-binding integrin a2b1 and the transitional matrix-binding integrins a5b1 and avb3.…”
mentioning
confidence: 99%